2022
DOI: 10.3389/fnagi.2022.809879
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Cellular Tagging in Young and in Early Cognitive Aging

Abstract: The ability to maintain relevant information on a daily basis is negatively impacted by aging. However, the neuronal mechanism manifesting memory persistence in young animals and memory decline in early aging is not fully understood. A novel event, when introduced around encoding of an everyday memory task, can facilitate memory persistence in young age but not in early aging. Here, we investigated in male rats how sub-regions of the hippocampus are involved in memory representation in behavioral tagging and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 83 publications
(146 reference statements)
3
21
0
Order By: Relevance
“…Aging-dependent decline in LTM is sensitively revealed with the ADMP task. This impairment in middle age is consistent with what has been shown in a cross-sectional study 24 and in a longitudinal study 23 in rats, both suggesting an encoding impairment in early aging. While encoding would also be affected by aging in the App NL-G-F/NL-G-F mice, the impairment in novelty-promoted memory at a younger age would suggest that early amyloid pathology may already affect production of PRP 29 , 75 and/or the circuits mentioned above for novelty detection in contributing to PRP.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Aging-dependent decline in LTM is sensitively revealed with the ADMP task. This impairment in middle age is consistent with what has been shown in a cross-sectional study 24 and in a longitudinal study 23 in rats, both suggesting an encoding impairment in early aging. While encoding would also be affected by aging in the App NL-G-F/NL-G-F mice, the impairment in novelty-promoted memory at a younger age would suggest that early amyloid pathology may already affect production of PRP 29 , 75 and/or the circuits mentioned above for novelty detection in contributing to PRP.…”
Section: Discussionsupporting
confidence: 90%
“…At the cellular level, we have recently shown that encoding of the ADMP task and novelty engage overlapping cell populations in CA1 and CA3 of the hippocampus 24 . Further analyses reveal that novelty, compared to familiarity, preferentially activates more cells in the distal CA1 and increases the overlapping cell population in distal CA1 and proximal CA3 24 . The proximal CA3–distal CA1 regions and connection have been implicated in object novelty or recognition 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Episodic memory (personal experiences) or episodic-like memory formation depends on the interactions among the medial temporal lobe, prefrontal cortex, prosencephalon basal, and diencephalic structures. It is meant to assess the integration of memories about when (time)/what (item)/where (spatial) information of items ( Tulving and Markowitsch 1997 ; Morris 2001 ; Daumas et al 2005 ; Dere et al 2005 ; Kart-Teke et al 2006 ; Kesner et al 2008 ; Gros et al 2022 ) and is more vulnerable to the effects of aging and cognitive disorders ( Robitsek et al 2008 ; Bishop et al 2010 ; Hamezah et al 2018 ).…”
mentioning
confidence: 99%